2021
DOI: 10.1016/j.eclinm.2021.101038
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational safety study on ChAdOx1 nCoV-19 corona virus vaccine (recombinant) use in healthcare workers- first results from India

Abstract: Background: We provide the first post-approval safety analysis of COVISHIELD in health care workers (HCWs) in northern India. Methods: This continuing prospective observational study (February 2021 to May 2022) enrolled participants 18 years receiving COVISHIELD vaccination. Primary outcome was safety and reactogenicity. Categories (FDA toxicity grading) and outcomes of adverse events following immunization (AEFIs) were recorded, causality assessment performed, and risk factors analysed. Findings: We present t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
59
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 22 publications
13
59
3
Order By: Relevance
“…We have found no signi cant association between age and AEFI, whereas some studies found age to be signi cantly associated with AEFI (24,25). Mohakuda (29). We have found signi cant association between gender and AEFI and number of females have reported more AEFI after both the doses as compared to males which is corroborated with some other studies (27,30).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…We have found no signi cant association between age and AEFI, whereas some studies found age to be signi cantly associated with AEFI (24,25). Mohakuda (29). We have found signi cant association between gender and AEFI and number of females have reported more AEFI after both the doses as compared to males which is corroborated with some other studies (27,30).…”
Section: Discussionsupporting
confidence: 85%
“…In the study conducted by Raches Ella et al(34),22.2% had at least one comorbid condition. Whereas there was statistically insigni cant association between the development of AEFI and comorbidity in studies byMohakuda et al (26) and Kaur et al(29).In our study, subjects with allergy reported more AEFI. Similar results were found by Kaur et al(29).…”
contrasting
confidence: 75%
See 3 more Smart Citations